A voltage-mode PID controller using a single CFOA and only grounded capacitors. (November 2018) - Ayten, Umut Engin; Yuce, Erkan; Minaei, Shahram
Abstract: A new voltage-mode (VM) proportional integral derivative (PID) controller employing only a single active component named Current Feedback Operational Amplifier (CFOA), two resistors and two grounded capacitors is proposed. The proposed PID controller employs a canonical number of only grounded capacitors without requiring any critical passive component matching conditions and cancellation constraints. It has high input and low output impedances; thus, it can be easily cascaded with other VM structures. It can be easily constructed by a single commercially available active element. Frequency-dependent non-ideal gain and parasitic impedance effects on the performance of the proposed PID controller are investigated. The performance of the proposed PID controller circuit is demonstrated by using PSPICE circuit simulation program and an experiment. Also, 0.18 μm CMOS TSMC technology parameters with ±2 V supply voltages are used. Total power dissipation of the proposed PID controller is 1.64 mW.